Sustainable Management of Wetlands: A case study of the Songor Ramsar and UNESCO Man and Biosphere Reserve in Ghana - Joseph Richmond Fianko; Helina S Dodd (Center for Journal Management and Publication, 2018)
This study on the Songor Ramsar and UNESCO Man and Biosphere Reserve in Ghana seeks to ascertain management method to promote sustainable management of wetlands.Â The findings clearly indicated that good management practices are employed in the management of the Songor Ramsar Site. The current approaches to management have focused on the harmonious fusion of modern scientific strategies and cultural and traditional methods. In the Songor Ramsar and UNESCO Man and Biosphere Reserve, traditional authorities have enacted traditional rites such as sacred groves and totems in the Ada East District which are strictly enforced to provide traditional regulatory support for their protection while modern conservation approaches in the Songor Wetland management utilizes all the laws in legal protected areas in Ghana. Management also embark on training programmes for users of the wetland resources in sustainable resource utilization to improve economic livelihood.Â Increased public education and sensitization on the economic importance of the Ramsar Site and the negative impact of environmental degradation has been part of the management strategies. The Public education is on environmentally sound management of waste within the Ramsar Site since the underlying causes of environmental degradation in the Songor Ramsar Site are mainly improper waste disposal, poor attitude of residents toward environmental conservation, wildfires and shoreline recession, inadequate public education on the impact of environmental degradation, fishing, and farming activities. The other factors identified include overgrazing, over exploitation of mangroves, predation, poaching and over fishing, and uncontrolled sand and salt winning